PENERAPAN AUDIT MANAJEMEN KINERJA PT. SUPERINDO UTAMA SURABAYA MENGGUNAKAN BALANCED SCORECARD - Rizky, Chandra Meithania; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to measure how the implementation of performance audit management on PT Superindo Utama Surabaya has been done by using Balanced Scorecard method which is based on 4 perspectives, so it can support the management of the company in achieving the mission and the vision of the company.This research iscarried out by using qualitative descriptive method which is supported by collecting the required datai.e.: documentation and direct interview to the informant. The obtained result of the analysis is comparedto the previous result of the analysis to find out whether there is an improvement to the performance of the company.Based on the analysis result which has been done in 2013-2014 periods, it has been found that the financial perspective applies the ROI standard and the Net Profit Margin shows well performance. The customer perspective shows quite good performance by the presence of customer retention, customer acquisition, and customer satisfaction.The internal business process perspective, companies can perform quite good innovation for the generated products. Moreover, the growth and learning perspective shows that the ability of the company in conducting the employeesâ performance assessment can be stated quite well which has been done by using the assessment of Employee Turn Over and Employee Training.Keywords: Performance Measurement, Balanced Scorecard